Effects of nurse‐led home‐based telephone support or home visits on cognitive function - Nanqi Mao; Fangyuan Xue; Wanyu Cai; Jiahong Li (Wiley, 2022)
Abstract Patients who have undergone carotid revascularization surgery have a high risk of postoperative cognitive decline, and home‐based care is the major form of postoperative management. Here, we aimed to compare the nurse‐led home‐based telephone support (NLHBTS) and home visits as additional postoperative care for patients who have undergone carotid revascularization surgery. The study recruited 172 patients, and 131 patients were randomly assigned to receive combined telephone support and home visits (intervention group) or home visits alone (control group) during the study period of 12 weeks. At baseline, 1 month, and 3 months, cognitive function was assessed using the Trail Making Test, Processing Speed Index, Boston Naming Test, Working Memory Index, Controlled Oral Word Association Test, and Hopkins Verbal Test. Sixty‐five patients in the intervention group and 66 in the control group completed the 1‐month treatment, and 49 in the intervention group and 48 in the control group completed the 3‐month treatment. The intervention group showed significant improvement in four of the six cognitive tests after the 3‐month treatment, whereas the control group only showed significant improvement in the Controlled Oral Word Association Test. Compared to the control group, significantly higher scores were achieved by the intervention group at 3 months in the Trail Making Tests (113 ± 23 vs. 128 ± 18, p = 0.001), Processing Speed Index (115 ± 15 vs. 108 ± 14, p = 0.020), Controlled Oral Word Association Test (51 ± 11 vs. 45 ± 9, p = 0.004), and Hopkins Verbal Learning Test (9.0 ± 1.6 vs. 8.3 ± 1.8, p = 0.046). NLHBTS, in combination with home visits, could facilitate the improvement of cognitive function in patients with carotid artery stenosis after surgery.